2014
DOI: 10.3349/ymj.2014.55.4.1036
|View full text |Cite
|
Sign up to set email alerts
|

Association between Serum 25-Hydroxyvitamin D Level and Insulin Resistance in a Rural Population

Abstract: PurposeA low serum 25-hydroxyvitamin D [25(OH)D] level in the blood has been correlated with an increased risk of diabetes mellitus; however, the association between serum 25(OH)D level and insulin resistance has not been established in a Korean rural population. The aim of this study was to investigate the independent association between serum 25(OH)D level and insulin resistance in rural Korean adults.Materials and MethodsThis study used data from the Korean Genome Epidemiology Study-Kangwha Study. In the 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
2
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 24 publications
(49 reference statements)
0
16
2
1
Order By: Relevance
“…The mean level of insulin in this study was 6.7 uIU/mL [ Table 3], which was equal with the results of the study on 324 Korean men. [41] Serum insulin level between normal SHBG phenotype when compared with variant SHBG phenotype was different (p < 0.05) [ Table 3]. These data indicate that serum insulin level is influenced by proteins polymorphism of SHBG.…”
Section: Discussionmentioning
confidence: 95%
“…The mean level of insulin in this study was 6.7 uIU/mL [ Table 3], which was equal with the results of the study on 324 Korean men. [41] Serum insulin level between normal SHBG phenotype when compared with variant SHBG phenotype was different (p < 0.05) [ Table 3]. These data indicate that serum insulin level is influenced by proteins polymorphism of SHBG.…”
Section: Discussionmentioning
confidence: 95%
“…In an East Asian population of 136 healthy Japanese males, Sun et al (36) found that the median 25(OH)D concentration was 36•5 nmol/l and that 78•7 % of the men were 25(OH)D deficient (<50 nmol/l). In 807 rural Korean adults, the mean serum 25(OH)D concentration was 64•5 nmol/l (75•25 nmol/l in men and 57•25 nmol/l in women) (12) . Choi et al (37) studied 260 Korean adolescents and found a mean concentration of 25(OH)D of 39•5 nmol/l (42•5 nmol/l in males and 36 nmol/l in females), while Tao et al (38) found that the mean 25(OH)D concentration was 51•75 nmol/l in 1382 non-diabetic Chinese female participants.…”
Section: Discussionmentioning
confidence: 99%
“…However, in recent years, increasing evidence has indicated that 25(OH)D may have additional functional roles. Several studies have indicated an association between low concentrations of serum 25(OH)D and insulin resistance (4)(5)(6) , although this relationship has been controversial (7)(8)(9)(10)(11)(12) . Moreover, BMI, blood glucose status and season are also known to influence the relationship between 25(OH)D and insulin resistance.…”
mentioning
confidence: 99%
“…There was an association between the severity of hypovitaminosis D and obesity 16 . The present study had showed that there is a significant negative correlation between obesity and hypovitaminosis.…”
Section: Discussionmentioning
confidence: 95%